2006
DOI: 10.2202/2161-2412.1001
|View full text |Cite
|
Sign up to set email alerts
|

Principals' Perceptions of Multicultural Education and School Climate

Abstract: Scholars of multicultural education urge school administrators to produce curricula in which the heterogeneity found in our public schools becomes an asset and not a barrier. In this survey research, we examined the extent to which secondary school principals in a southeastern state positively viewed the values and principles of multicultural education with regard to shaping their school climate to make certain it reflects the ideals of respect, trust, and high morale for all students. We found that secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Despite educational reforms that have attempted to address these issues, inequities in education for diverse students with special needs continue to dominate (Daniels, 1998). To address this issue, school administrators must ensure teachers are prepared with an understanding of the benefits of multiculturalism and a realization of how ignoring students' culture could contribute to their placement in special education programs (McCray, Alston, & Beachum, 2006;Williams, Beachum, Obiakor, & McCray, in press). Hence, school administrators must understand their roles in the teaching and learning process of multicultural students, especially those with special education needs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite educational reforms that have attempted to address these issues, inequities in education for diverse students with special needs continue to dominate (Daniels, 1998). To address this issue, school administrators must ensure teachers are prepared with an understanding of the benefits of multiculturalism and a realization of how ignoring students' culture could contribute to their placement in special education programs (McCray, Alston, & Beachum, 2006;Williams, Beachum, Obiakor, & McCray, in press). Hence, school administrators must understand their roles in the teaching and learning process of multicultural students, especially those with special education needs.…”
Section: Resultsmentioning
confidence: 99%
“…At the school level, the school administrator is the designee appointed to ensure that each student receives a quality education (Williams et al, 2002). The effectiveness of a school's educational program is ultimately determined by the leadership and attitude of the school administrator (McCray, Alston, & Beachum, 2006). Earlier, Goor and Schwenn (1997) asserted that educational leadership is the number one variable associated with effective schools.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these theories will only be valid in cultures where cultural dimensions are similar to those of the U.S. culture. The growing international commonality in educational policy and in institutional structures makes culture and cultural differences an important area gaining increased significance (Leeman, 2003;McCray, Alston, & Beachum, 2006).…”
Section: Theories Of Cross-cultural Leadershipmentioning
confidence: 99%
“…It is, therefore, assumed if leaders in intercultural schools are to make a difference then they must leam to understand the cultural influences affecting their schools. This calls for the development of leader authenticity (McCray, Alston, & Beachum, 2006).…”
Section: Cross-cultural Educational Leadershipmentioning
confidence: 99%
“…Unfortunately, the idea of implementing any form of a multicultural curriculum in schools was not the main priority of many school administrators, especially in schools in the Deep South. In fact, some of the administrators' goals during the apex of school integration were to prevent the formation of a unitary school system (McCray, Alston, & Beachum, 2006). Capper (1993) observed that, even today, "to some administrators, the idea of education that is multicultural and social reconstructionist conjures up images of teaching their students how to be radical student demonstrators, reminiscent of the sixties" (p. 288).…”
Section: Introductionmentioning
confidence: 99%